Mesenchymal stem cell exosomal tsRNA-21109 alleviate systemic lupus erythematosus by inhibiting macrophage M1 polarization. (November 2021) - Dou, Rui; Zhang, Xiulei; Xu, Xiangdong; Wang, Pei; Yan, Beizhan
Highlights: Mesenchymal stem cells derived exosomes suppressed M1-type polarization macrophages. Small RNA-Seq identified tsRNA-21109 up-regulated in macrophage to response MSC-Exo. Inhibiting tsRNA-21109 expression promote M1-type polarization macrophages. tsRNA-21109 expression was associated with clinical SLE patient data. Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with M1-type macrophage activation. Mesenchymal stem cells (MSCs) therapies have shown promise in models of pathologies relevant to SLE, while the function and mechanism of MSC-derived exosomes (MSC-exo) were still unclear. We aimed to interrogate the effect of MSC-exo on M1-type polarization of macrophage and investigate mechanisms underlying MSC-exo. Exosomes were isolated from MSC and the effect of MSC-exo on macrophage polarization was evaluated. The key tRNA-derived fragments (tRFs) carried by exosomes were identified by small RNA sequencing and verified in clinical samples. The effect of exosomal-tRFs on macrophage polarization was examined. In this study, MSC-exo dramatically suppressed expression of M1 markers, and reduced the levels of TNF-α and IL-1β, while increased M2 markers in macrophages. A total of 243 differently expressed tRFs (DEtRFs) were identified between MSC-exo treated and untreated macrophage, among which 103 DEtRFs were up-regulated in response to MSC-exo treatment, including tsRNA-21109. The target genes of tsRNA-21109 were mainly enriched in DNA transcription-related GO function, and mainly involved in inflammatory-related pathways, including Rap1, Ras, Hippo, Wnt, MAPK, TGF-beta signaling pathway. The tsRNA-21109 was lowly expressed in clinical samples and was associated with the patient data in SLE. Compared to the normal MSC-exo, the tsRNA-21109-privative MSC-exo up-regulated M1 marker (CD80, NOS2, MCP1) and down-regulated M2 marker (CD206, ARG1, MRC2), also increased the levels of TNF-α and IL-1β in macrophages. Western blot and immunofluorescence confirmed that the proportion of CD80/ARG-1 was increased in macrophages treated with tsRNA-21109-privatived MSC-exo compared to that with control MSC-exo. In conclusion, MSC-exo inhibited the M1-type polarization of macrophages, possibly through transferring tsRNA-21109, which may develop as a novel therapeutic target for SLE.